Analysis of life cycle and carbon footprint in the production process jeans. Case study producing plants southern region hidalgo, México (2020)
Climate change is presented as one of the great challenges of the 21st century. Being able to measure their progress, setbacks and opportunities is key to generating effective strategies in organizations. The Carbon Footprint is an indicator capable of providing this information. Quantification permits the calculation of direct and indirect emissions of greenhouse gases. That is why this article you can recognize a strategic nature, whose content is not intended to delve into the theoretical concepts but give practical guidelines necessary for a company to be able to justify initiating and interpreting projects management and calculation of carbon footprint in organizations and products. The results provide the seed needed for any business to have its environmental assessment for emissions of greenhouse gases. Keywords: Carbon footprint, Life-cycle assessment, environment. JEL Classification: Q51, Q53, Q56 Received: 28/05/2020. Accepted: 03/11/2020.  Published: 01/12/2020